Drug formulations for use in low-temperature hyperthermia therapy, and their preparation methods and uses
Patent Information
- Application Number
- JP2022572693
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-13
- Filing Date
- 2022-07-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-07-05
AI Technical Summary
【0033】 本発明で開示するナノカーボン鉄複合製剤は、腫瘍低温温熱治療に使用ができる。本発明に基づく医薬組成物は、低温温熱治療時、投与量の有意な低減、副作用の発生低減に繋がる。また、本発明に基づく複合製剤を用いた温熱療法の実施温度は低く、周囲の正常組織を損傷しにくく、ナノカーボン温熱治療時の副作用を軽減する。さらに、ナノカーボン鉄複合製剤が近赤外照射と協同効果があることを証明した。低温温熱治療の手段及び技術効果を踏まえ、本発明は広範な臨床意義を持っている。
Smart Images

Figure 0007641992000005 
Figure 0007641992000006 
Figure 0007641992000007
Abstract
Description
[Technical field]
[0001] The present invention belongs to the field of pharmaceutical technology, and specifically relates to a drug formulation for use in low-temperature hyperthermia therapy, and its preparation method and use. [Background technology]
[0002] Photothermal therapy is a new type of tumor treatment method that has recently emerged. It has a very wide application prospect due to its low invasiveness, high therapeutic effect, and low side effects. In the process of developing hyperthermia reagents, carbon nanotubes, graphene, carbon quantum dots, and fullerenes are currently the focus of research. The carbon atoms in these materials are SP 2 The hybridization forms a covalent bond, which spreads around to form a honeycomb-like six-membered ring structure, and the n-electrons are concentrated on the ring, forming a large delocalized n-bond, so it is called SP 2 The hybridization gives these carbon materials many special properties, including the absorption of NIR light, which makes them ideal candidates for hyperthermia therapy, as they can rapidly convert light energy into heat after absorbing NIR light, killing tumor cells.
[0003] With the accumulation of research data over a long period of time, the development of hyperthermia reagents has made great progress, among which some progress has been made in improving the targeting of surface modification and in toxicity research, but there are still many problems in the research, limiting clinical application. The main defects are as follows: (1) The preparation process is difficult to control. The crude products of carbon nanotubes, graphene, and fullerene contain many impurities, which may cause toxic side reactions in the body, and have poor hydrophilicity, which is unfavorable for dispersion in water, so purification and surface modification are necessary. The purification process is mainly to remove impurities, improve purity, and reduce the risk of toxic side effects caused by impurities. The surface modification is mainly the modification of the surface group of carbon, which makes it favorable for dispersion in water and improves the conversion efficiency of NIR in hyperthermia. However, in the process of reagent development, it was found that these carbon materials are mixtures of a certain particle size range, and it is difficult to control the consistency between lots during the purification and surface modification process, which leads to property differences between product lots, affects the comprehensive evaluation, and hinders the development of subsequent tests. (2) It is difficult to control the particle shape and size. Among the above materials, carbon nanotubes have a tubular structure and require passivation treatment at both ends during the preparation process, but they are usually prone to incomplete processing, leaving needle-like tips. After administration, these sharp tips are likely to break through the blood vessel wall and enter the cell nucleus, which has potential genotoxicity. (3) Poor targeting and insufficient precision. After local administration, carbon nanotubes, graphene, carbon quantum dots, and fullerenes have poor targeting and are enriched around the tumor, while some are dispersed around the normal tissue. During hyperthermia treatment, even carbon scattered around the normal tissue will generate heat, causing burns to the normal tissue. (4) High cost. Due to the complex preparation process, the high cost associated with the preparation, purification, chemical modification and other processes limits its large-scale production and clinical application. Under the above application background, the application of hyperthermia preparations has long remained in the early exploration stage, and no safe, stable and controllable reagent has entered the clinical application stage that can be used safely and effectively by patients.
[0004] The principle of nanocarbon heating is that nanocarbon can efficiently absorb near-infrared radiation (NIR), which is converted into heat, but biological tissues have low absorption of NIR (high transmittance), and so conversion to heat is low. Therefore, by utilizing the above difference, nanocarbon can be used as a hyperthermia medium. After injection into a cancer lesion, the NIR incident from outside penetrates the normal tissue on the surface and reaches the cancer lesion, where it heats the nanocarbon, raising the temperature of the tumor tissue and creating a hyperthermia effect. However, the temperature required for nanocarbon hyperthermia is high (50°C or higher) to necrotize and coagulate tumor cells, which tends to damage nearby normal tissue cells. The drug nanocarbon iron developed by the authors is a nanosuspension formulation with nanocarbon as a carrier and divalent iron ions as an active ingredient. It is an innovative anti-cancer drug with a mechanism of action in which nanocarbon iron (CNSI-Fe) is injected locally into cancer tissue, and then enters the cancer cell through the iron channel overexpressed in the cancer cell membrane. When a large amount of iron ions enters cancer cells that are rich in hydrogen peroxide (H2O2), a Fenton reaction occurs with H2O2, generating a large amount of hydroxyl radicals (OH). ·OH has extremely strong oxidizing properties, and reacts with unsaturated polyfatty acids (UPFAs) in cells to generate a large amount of highly destructive lipid hydrogen peroxide (L-OOH), which produces lipid reactive oxygen species (Lipid-ROS). Lipid-ROS destroys cell organelles, leading to cell destruction and causing iron death (ferroptosis).
[0005] CNSI-Fe2 + +H2O2-ROS (·OH) -L-ROS-Ferroptosis The influencing factors of the Fenton reaction are pH value, H2O2 dosage, Fe 2+These are the dosage, reaction time and reaction temperature. If the reaction temperature is increased without changing other conditions, the reaction rate will be faster and the reaction will be stronger. If nanocarbon iron is locally injected into cancer tissue and then near-infrared light is irradiated to increase the temperature, the Fenton reaction of iron ions can be enhanced. However, the temperature at which hyperthermia is currently performed using conventional nanocarbon preparations is usually above 50°C, and at temperatures higher than 50°C, the surrounding skin is likely to be burned. Therefore, there is an urgent need in this field for a hyperthermia preparation that can fully utilize nanocarbon and is easy for patients to use without burning the skin. Summary of the Invention [Problem to be solved by the invention]
[0006] In order to overcome the above technical shortcomings, the present invention provides a new use of nanocarbon iron suspension injection, specifically adopting the following technical scheme:
[0007] In a first aspect, the present invention provides a use of a nanocarbon-iron composite formulation in the preparation of a tumor thermotherapy drug in combination with near-infrared light.
[0008] Furthermore, the combined use with near-infrared light means that tissue is heated with near-infrared light, and the wavelength of the near-infrared light is 780 to 2600 nm, and according to a preferred embodiment, the wavelength of the near-infrared light is 780 to 1400 nm.
[0009] Furthermore, the nanocarbon iron composite preparation contains a nanocarbon suspension injection solution and injectable ferrous sulfate, and the mass ratio of the two is 20-100:3-300. According to a preferred embodiment, the mass ratio of the two is 50:7.5-180. According to a further preferred embodiment, the mass ratio of the two is 50:15-45.
[0010] Furthermore, when the nanocarbon iron composite preparation is used, the nanocarbon suspension injection solution and the injectable ferrous sulfate are mixed uniformly in the above-mentioned mass ratio, and the pH value is 2 to 7, and according to a preferred embodiment, the pH is 3 to 5.5.
[0011] Furthermore, the nanocarbon iron suspension injection solution contains nanocarbon, a suspension aid, physiological saline, a pH adjuster, sodium chloride, and water for injection, and further contains 20-100g of nanocarbon, 17-30g of suspension aid, 2-4g of pH adjuster, and 8-10g of sodium chloride per 1000mL of nanocarbon suspension injection solution, and the rest is water for injection. Furthermore, according to one embodiment, the nanocarbon suspension injection solution contains 50g of nanocarbon, 20g of suspension aid, 3g of pH adjuster, and 9g of sodium chloride per 1000mL of nanocarbon suspension injection solution, and the rest is water for injection.
[0012] Furthermore, the nanocarbon is one or more of nanocarbon particles, carbon nanotubes, carbon quantum dots, graphene, fullerene, nanocarbon rods, and nanocarbon fibers. According to a preferred embodiment, the nanocarbon is nanocarbon particles or graphene. Furthermore, according to one embodiment, the nanocarbon is carbon black.
[0013] Furthermore, the iron salt is one or more of ferrous sulfate, ferrous sulfate, ferrous chloride, ferrous trichloride, ferrous gluconate, ferrous sucrose, ferrous ammonium citrate, ferrous succinate, ferrous sorbitol, and ferrous fumarate. According to a preferred embodiment, the iron salt is ferrous sulfate, ferrous sulfate, ferrous chloride, or ferrous trichloride. According to a further embodiment, the iron salt is ferrous sulfate.
[0014] Furthermore, the suspending agent is any one or several of poloxamer, polyvinylpyrrolidone C30 (PVP C30), and polysorbate 80. According to a preferred embodiment, the suspending agent is a poloxamer.
[0015] Furthermore, the pH adjuster is any one of sodium citrate, sodium acetate, sodium borate, sodium phosphate, and sodium bicarbonate. According to a preferred embodiment, the pH adjuster is sodium citrate, which forms a complex with ferrous ions and / or iron ions in the iron salt.
[0016] Furthermore, the preparation method of the above nanocarbon suspension injection includes the following steps: 1) Add the above amount of sodium chloride to 90% v / v of water for injection and stir until completely dissolved to obtain a salt solution. 2) The pH adjuster and suspension aid are added in the prescribed amounts to the salt solution obtained in step 1), and stirred until completely dissolved to obtain a secondary raw material liquid. 3) Add the compounded amount of pretreated nanocarbon to the auxiliary raw material liquid obtained in step 2), stir to mix uniformly, and add the remaining water for injection to adjust the volume to obtain a constant volume solution. 4) The constant volume solution obtained in 3) is then homogenized at a rotation speed of 15,000 to 20,000 rpm for 3 to 10 minutes, and homogenized 1 to 5 times at a pressure of 15,000 to 30,000 psi. After filling and sealing, the container is steam sterilized at 115 to 130°C for 10 to 30 minutes to complete the process.
[0017] Furthermore, in step 3), the pretreatment includes degreasing the nanocarbon with ethyl acetate, and then washing with an 8-15% v / v HNO3 aqueous solution, where the mass of the nanocarbon: the volume of the HNO3 aqueous solution is 1g:3-5 / ml. Thereafter, the nanocarbon is washed with water until it is close to neutral, and then washed with a 0.08-0.15 mol / L NaOH aqueous solution. Here, the mass of the nanocarbon: the volume of the NaOH aqueous solution is 1g:3-5 / ml, and then the nanocarbon is washed with water until it is close to neutral. Furthermore, the mass of the nanocarbon: the volume of the HNO3 aqueous solution is 1g:4 / ml. Furthermore, the mass of the nanocarbon described in step S1: the volume of the NaOH aqueous solution is 1g:4 / ml. According to a preferred embodiment, the HNO3 is a 10% v / v HNO3 aqueous solution.
[0018] Furthermore, in step 4), the homogenization speed is 18,000 rpm, and the homogenization time is 5 minutes.
[0019] Furthermore, in step 4), the homogenization pressure is 20,000 psi, and the homogenization number is 3.
[0020] Furthermore, in step 4), the sterilization temperature is 121° C. and the sterilization time is 15 minutes.
[0021] Furthermore, the ferrous sulfate for injection is a freeze-dried powder of ferrous sulfate for injection. Furthermore, the freeze-dried powder of ferrous sulfate for injection is composed of ferrous sulfate heptahydrate, sulfuric acid, and water for injection. The mass ratio of ferrous sulfate heptahydrate:sulfuric acid:water for injection is 0.1-0.2g:0.4-0.85μg:2g. According to a preferred embodiment, the sulfuric acid is sulfuric acid with a mass percentage content of 1%.
[0022] Furthermore, the preparation method of the ferrous sulfate lyophilized powder for injection includes the following steps:
[0023] S1) During the preparation process, continuously fill the water for injection (90% blend volume) with N2 at a nitrogen gas flow rate of 4.0 to 5.0 m3 / h at the liquid surface.
[0024] S2) Then, sulfuric acid is added to adjust the pH to 2.4 to 2.8. According to a preferred embodiment, the pH is adjusted to 2.4.
[0025] S3) Stir well to dissolve the prescribed amount of ferrous sulfate heptahydrate.
[0026] S4) The remaining sulfuric acid is added to adjust the pH to 2.8 to 3.0, and the remaining purified water is added to the total volume, followed by stirring uniformly to obtain a ferrous sulfate solution. According to a preferred embodiment, the pH is adjusted to 2.8.
[0027] S5) The obtained drug solution is filtered through a micropore filter, then filled and freeze-dried, and a plug is inserted under vacuum conditions, and the lid is closed, and the process is completed. According to a preferred embodiment, the pore size of the micropore filter is 0.45 μm.
[0028] Furthermore, in S5, the operation of the freeze-drying step is specifically as follows.
[0029] S51 Pre-freezing: Rapidly lower the temperature to -10 to -5°C, keep warm for 1 to 3 hours, and further rapidly lower the temperature to -50 to -40°C, keep warm for 1 to 3 hours. According to a preferred embodiment, the temperature is lowered to -5°C, and kept warm for 2 hours. According to a preferred embodiment, the temperature is lowered to -45°C, and kept warm for 2 hours.
[0030] S52 Drying: S521: After the temperature is gradually increased from -50 to -40°C to -20 to -10°C, the mixture is kept at -20 to -10°C and 80 to 120 mtorr for 2 to 4 hours. According to a preferred embodiment, the temperature is gradually increased from -45°C to -15°C, and the mixture is kept at -15°C and 100 mtorr for 3 hours.
[0031] S522: After 1 to 3 hours, the temperature is gradually increased from -20 to -10°C to -10 to 0°C, and the temperature is maintained at 80 to 120 mtorr and -10 to 0°C for 1 to 3 hours. According to a preferred embodiment, after 2 hours, the temperature is gradually increased to -15°C to -5°C, and the temperature is maintained at 100 mtorr and -5°C for 2 hours.
[0032] S523: After 3 to 6 hours, the temperature is increased gradually from 0°C to 20°C, and the temperature is maintained at 80 to 120 mtorr and 20°C for 3 to 6 hours. According to a preferred embodiment, after 4 hours, the temperature is increased gradually from 0°C to 20°C, and the temperature is maintained at 100 mtorr and 20°C for 4 hours. Effect of the Invention
[0033] The nanocarbon-iron composite preparation disclosed in the present invention can be used in tumor cryo-hyperthermia treatment. The pharmaceutical composition according to the present invention leads to a significant reduction in the dosage and the occurrence of side effects during cryo-hyperthermia treatment. In addition, the temperature at which hyperthermia is performed using the composite preparation according to the present invention is low, which is less likely to damage surrounding normal tissues and reduces side effects during nanocarbon hyperthermia treatment. Furthermore, it has been proven that the nanocarbon-iron composite preparation has a synergistic effect with near-infrared irradiation. In view of the means and technical effects of cryo-hyperthermia treatment, the present invention has broad clinical significance. [Brief description of the drawings]
[0034] [Figure 1]Tumor volume growth curves of SMMC-7721 hepatocellular carcinoma nude mouse xenograft tumors by group. [Diagram 2] Tumor volume growth curves for HCT-116 colon cancer nude mouse xenograft tumors by group. [Diagram 3] Tumor volume growth curves for MDA-MB-231 breast cancer nude mouse xenograft tumors by group. [Figure 4] Hydroxyl radical waveform diagram of SMMC-7721 liver cancer tumor tissue. [Diagram 5] Inhibitory effect on lymph node metastasis of H22 hepatocellular carcinoma cells by group. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] (1) Implementation form Example 1: Preparation of nanocarbon suspension injection The nanocarbon suspension injection solution contains 50g of nanocarbon, 20g of suspension aid, 3g of pH adjuster, 9g of sodium chloride, and the remainder is water for injection per 1000mL of the nanocarbon suspension injection solution. The method for preparing the nanocarbon suspension injection solution is as follows: 1) adding a blended amount of sodium chloride to the above blended amount of 90% v / v water for injection and stirring until completely dissolved to obtain a salt solution; 2) adding a blended amount of a pH adjuster and a suspension aid to the salt solution obtained in step 1) and stirring until completely dissolved to obtain an auxiliary raw material liquid; 3) adding a pretreated blended amount of nanocarbon obtained in step 2) to the auxiliary raw material liquid obtained in step 2), stirring uniformly, and then adding the remaining constant volume water for injection to obtain a constant volume liquid; 4) then rotating the constant volume liquid obtained in step 3 at a rotation speed of 18,000 rpm for 5 minutes. The process involves homogenizing the mixture for 1 min at 20,000 psi, homogenizing it three times at 20,000 psi, filling the containers, capping them, and steam sterilizing them at 121°C for 15 min.
[0036] Embodiment 2: Preparation of Ferrous Sulfate for Injection The freeze-dried powder of ferrous sulfate for injection is composed of ferrous sulfate heptahydrate, sulfuric acid and water for injection, in which the mass ratio of ferrous sulfate heptahydrate:sulfuric acid with a mass percentage of 1%:water for injection is 0.149g:0.4-0.85μg:2g, and in a preferred embodiment, the sulfuric acid is sulfuric acid with a mass percentage content of 1%. The preparation method is as follows:
[0037] S1: N2 is continuously filled below the liquid surface during preparation of 90% water for injection, and the nitrogen gas flow rate is controlled to 4.0 to 5.0 m3 / h. S2: Sulfuric acid is added to adjust the pH to 2.4. S3: The amount of ferrous sulfate heptahydrate is thoroughly stirred to dissolve. S4: The remaining sulfuric acid is added to adjust the pH to 2.8, and the remaining purified water is added to the total volume, and the mixture is stirred uniformly to obtain a ferrous sulfate drug solution. S5: The obtained drug solution is filtered through a 0.45 μm micropore filter, then filled, freeze-dried, and a plug is inserted under vacuum conditions, and the lid is closed to complete the process. Here, the freeze-drying process is specifically as follows.
[0038] S51 Pre-freezing: Rapidly cool to -5°C, keep warm for 2 hours, then rapidly cool to -45°C and keep warm for 2 hours. S52 Drying: S521: After 3 hours, increase temperature from -45°C to -15°C at a gradient, keep warm at 15°C and 100mtorr for 3 hours, S522: After 2 hours, increase temperature from -15°C to -5°C at a gradient, keep warm at 100mtorr and -5°C for 2 hours, S523: After 4 hours, increase temperature from 0°C to 20°C at a gradient, keep warm at 100mtorr and 20°C for 4 hours.
[0039] Embodiments 3 to 22 Tumor hyperthermia using nanocarbon suspension injections with different compounding ratios, injectable ferrous sulfate, and different near-infrared light JPEG0007641992000001.jpg145170
[0040] (2) Test Example 1. Sample: 1) Cell line SMMC7721 hepatoma cells, HCT116 colon cancer cells, MDA-MB-231 mammary adenocarcinoma cells, mouse-derived hepatoma H22 cells 2) Cell culture medium DMEM medium for cells, RMPI1640 medium, fetal bovine serum (FBS), cell digestion solution pancreatin, penicillin-streptomycin mixture, phosphate buffer (PBS, pH 7.4) 3) Test animals BalB / c-nu mice, female, 5-7 weeks old, weighing 20±2g. They were allowed to drink water and eat food ad libitum during the test. They were exposed to light for 12 hours every day. They were kept in a cage with dividers and independent ventilation means, with 5 mice per cage. SPF Balb / c mice, female, 4-6 weeks old, weighing 20±2g. Drink water and eat food freely during the test. Light is irradiated for 12 hours every day. 5 mice per cage, kept in a cage with a partition and an independent ventilation means. 4) Testing chemicals and major equipment Nanocarbon iron suspension injection of embodiment 4, nanocarbon iron suspension injection of embodiment 8, nanocarbon suspension injection (concentration is the same as in embodiments 4 and 8), 0.9% sodium chloride injection, blower dryer, thermostatic water bath, biological optical microscope, thermostatic incubator, pure water meter, high-pressure sterilization kettle, clean bench, electronic balance, 808 nm near-infrared hyperthermia treatment device, 1064 nm laser hyperthermia treatment device, infrared hyperthermia treatment device, electron spin resonance spectrometer (ESR)
[0041] 2. Test method: 1) Cellular testing Cells in the logarithmic growth phase are harvested, counted, and the cell density adjusted to 30,000 cells / ml. 1 ml is placed in a 25x25 mm glass dish and incubated at 37°C with 5% CO2 for 24 h. The cells are divided into a negative group, a near-infrared irradiation group, a nanocarbon iron group, a nanocarbon near-infrared irradiation group (37°C, 42°C, 45°C, 48°C, 50°C), and a nanocarbon iron near-infrared irradiation group (37°C, 42°C, 45°C, 48°C, 50°C), with three groups in each group. The negative group and the near-infrared irradiation group are replaced with new culture medium, while the nanocarbon iron group, the nanocarbon near-infrared irradiation group, and the nanocarbon iron near-infrared irradiation group are replaced with culture medium containing nanocarbon or nanocarbon iron. The nanocarbon near-infrared irradiation group and the nanocarbon iron near-infrared irradiation group are irradiated to the desired temperature with an 808 nm near-infrared thermotherapy device and maintained at the same temperature for 10 min. The irradiation time of the near-infrared irradiation group was the same as that of the test group with the longest irradiation time. After the end of irradiation, the cells were cultured for 48 hours. The cells were digested with pancreatin and counted to calculate the cell inhibition rate.
[0042] 2) Tumor growth inhibition test Harvest the cells in the logarithmic growth phase and adjust the cell suspension concentration to 3x10 cells. 7 The cells were then administered subcutaneously to the right upper limb of nude mice at a concentration of 0.1 mL / mouse (approximately 3 x 10 cells / mL). 6 The tumor volume of the inoculated mice was 100 mm on average. 3 When the tumor-bearing mice reached the target tumor size, they were randomly divided into groups, namely, a negative control group, a near-infrared irradiation group, a nanocarbon iron group, a nanocarbon near-infrared irradiation group, and a nanocarbon iron near-infrared irradiation group (using the nanocarbon iron mixed injection solution in embodiment 4). The administration method was intratumoral administration, with an administration volume of 50 μL per administration, and a second administration was given at an interval of two days, for a total of two administrations. 10 min after the drug was injected into the tumor, the nanocarbon near-infrared irradiation group and the nanocarbon iron near-infrared irradiation group were irradiated with 808 nm near-infrared light at a power density of 0.5 W / cm. 2 The irradiation time was 30 minutes, and the temperature was maintained at about 45°C. The near-infrared irradiation group was irradiated for the same period. The tumor volume of the mice was measured every week. The volume was calculated using the following formula: volume = (length x width). 2 ) / 2. Observation time is 21 days.
[0043] 24 hours after near-infrared irradiation, tumor tissues are collected, 0.9% sodium chloride injection is added, a 10% homogenate is prepared, a capture agent is added, and hydroxyl radicals are detected by ESR.
[0044] 3) Lymph node metastasis inhibition test Milky white ascites from H22 liver cancer-bearing mice was extracted, added to physiological saline, resuspended by centrifugation, and the cells were counted at 3x10 7 The solution is adjusted to 50 μL / mL and subcutaneously inoculated into the left hind foot pad of Balb / c mice, 50 μL per mouse, to obtain a mouse model of cancer lymph node metastasis. When the tumor diameter reaches 6-8 mm, and there is no ulcer or necrosis, the mice are treated. The mice are randomly divided into 5 groups, namely, a negative control group, a nanocarbon iron group, a near-infrared irradiation group, a nanocarbon near-infrared irradiation group, and a nanocarbon iron near-infrared irradiation group, with 7 mice in each group (using the nanocarbon iron suspension injection solution of embodiment 8). The administration method is intratumoral administration, with an administration volume of 50 μL / time, and a second administration is performed at an interval of 2 days, for a total of two administrations. 10 min after the drug is injected into the tumor, the nanocarbon near-infrared irradiation group and the nanocarbon iron near-infrared irradiation group are irradiated with 1064 nm near-infrared light to the popliteal lymph nodes of the left hind leg of the mice, with a power density of 0.5 W / cm. 2 The exposure time was 30 minutes, and the temperature was maintained at about 45°C. The near-infrared exposure group was exposed for the same period. Two weeks after exposure, the mice were sacrificed, and the popliteal lymph nodes were collected and weighed.
[0045] 3. Test results: 1) Cellular testing Near-infrared irradiation group had no significant killing effect on SMMC7721 liver cancer cells, HCT116 colon cancer cells, and MDA-MB-231 breast cancer cells, and the inhibition rates were all less than 10%. The inhibition rates of the effect of simple nanocarbon iron on SMMC7721 liver cancer cells, HCT 116 colon cancer cells, and MDA-MB-231 breast cancer cells were 40.15±2.98%, 34.97±1.67%, and 32.85±3.07%, respectively.
[0046] The inhibition rates of the nanocarbon near-infrared irradiation group and nanocarbon iron near-infrared irradiation group for the three types of cells are shown in Table 1-3. There is almost no effect on the cells at temperatures of 37℃ and 40℃, and the inhibition rate gradually increases as the temperature rises. When the temperature is 42℃ or higher, the inhibition rate of nanocarbon iron near-infrared irradiation increases significantly, which is superior to that of simple nanocarbon iron and nanocarbon iron near-infrared irradiation group at the same temperature. When the temperature of the nanocarbon near-infrared irradiation group reaches 50℃, the inhibition rate of the three types of cells reaches 90% or more, and when the temperature of the nanocarbon iron near-infrared irradiation group reaches 45℃, the inhibition rate reaches 90% or more.
[0047] Table 1. Inhibition rate of SMMC7721 liver cancer cells in the nanocarbon near-infrared irradiation group and the nanocarbon iron near-infrared irradiation group JPEG0007641992000002.jpg68170
[0048] Table 2. Inhibition rate of HCT116 colon cancer cells in the nanocarbon near-infrared irradiation group and the nanocarbon iron near-infrared irradiation group JPEG0007641992000003.jpg67170
[0049] Table 3. Inhibition rate of MDA-MB-231 breast cancer cells in the nanocarbon near-infrared irradiation group and the nanocarbon iron near-infrared irradiation group JPEG0007641992000004.jpg68170
[0050] 2) Tumor growth inhibition test The growth inhibitory effects of nanocarbon iron, nanocarbon near-infrared irradiation, nanocarbon iron near-infrared irradiation, and near-infrared irradiation on subcutaneously transplanted tumors of SMMC7721 liver cancer cells, HCT116 colon cancer cells, and MDA-MB-231 breast cancer cells in nude mice are discussed (Figures 1-3). As a result, at the end of the observation period, no significant inhibitory effect was observed on the subcutaneously transplanted tumors of the three cell types by simple near-infrared irradiation. The inhibitory rates of the subcutaneously transplanted tumors of the three cell types by nanocarbon iron were 48.57%, 52.03%, and 45.79%, respectively, the inhibitory rates of the subcutaneously transplanted tumors of the three cell types by nanocarbon near-infrared irradiation were 53.81%, 48.06%, and 49.35%, respectively, and the inhibitory rates of the subcutaneously transplanted tumors of the three cell types by nanocarbon iron near-infrared irradiation were 90.78%, 90.14%, and 93.3%, respectively. Nanocarbon iron near-infrared irradiation has a significant statistical difference compared to simple nanocarbon iron or nanocarbon near-infrared irradiation. According to the Kanezawa formula, when the q values of nanocarbon iron near-infrared irradiation are all greater than 1, it is suggested that there is a synergistic effect of nanocarbon iron near-infrared irradiation, which leads to an enhancement of the anti-cancer effect of nanocarbon iron and nanocarbon hyperthermia therapy.
[0051] At the same time, the hydroxyl radical content in the animal tumors of each group was compared (Figure 4). As a result, Figure 4a shows a sample without any treatment, and Figures 4b and 4d show that nanocarbon near-infrared irradiation and near-infrared irradiation did not lead to significant hydroxyl radical generation, while the hydroxyl radical content in the tumors of the nanocarbon iron group (Figure 4c) and nanocarbon iron near-infrared irradiation group (Figure 4e) was the highest, about twice that of the nanocarbon iron group. Therefore, it is suggested that after nanocarbon iron near-infrared irradiation, the temperature in the tumor is effectively increased, which increases the efficiency of the Fenton reaction and leads to the generation of more hydroxyl radicals.
[0052] 3) Lymph node metastasis inhibition test The inhibitory effects of nanocarbon iron, nanocarbon near-infrared irradiation, nanocarbon iron near-infrared irradiation, and near-infrared irradiation on lymph node metastasis of H22 hepatocellular carcinoma cells are discussed (Figure 5). As a result, no significant change was observed in lymph node weight in the near-infrared irradiation group compared to the negative group ("*": p<0.05, "**": p<0.01). The lymph node weights of the nanocarbon iron group, nanocarbon near-infrared irradiation group, and nanocarbon iron and infrared irradiation group all significantly decreased (p<0.01). Nanocarbon iron near-infrared irradiation had the strongest inhibitory effect on lymph node metastasis, with the weight of metastatic lymph nodes being the lightest, and there was a significant statistical difference in both cases compared to simple nanocarbon iron or nanocarbon near-infrared irradiation (p<0.05). According to the Kaneishi formula, when the q value of nanocarbon iron near-infrared irradiation exceeds 1, it is suggested that there is a synergistic effect of nanocarbon iron near-infrared irradiation, which leads to an enhanced effect of nanocarbon iron and nanocarbon hyperthermia on lymph node metastasis inhibition.
[0053] Finally, the above embodiments are only for illustrating the technical solutions of the present invention, and are not limited thereto. Although the present invention has been described in detail with reference to the above embodiments, in order to facilitate understanding by general technical personnel in the same technical field, the technical solutions described in the above embodiments may be modified or the technical features may be replaced with equivalent modifications, but such modifications or replacements shall not cause the technical solutions to depart from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. 1. A method for using a nanocarbon-iron composite formulation in the preparation of a tumor thermotherapy drug in combination with near-infrared light heating of tissue, comprising: The combination of heating the tissue with near-infrared light refers to heating the tissue by heating a nanocarbon-iron composite preparation with near-infrared light; The wavelength of the near-infrared light is 780 to 2600 nm, The heating temperature of the nano carbon iron composite preparation in the near infrared light is 48°C; The nanocarbon iron composite preparation comprises a nanocarbon suspension injection solution and ferrous sulfate for injection, and the mass ratio of the two is 20-100: 3-300; The ferrous sulfate for injection is a freeze-dried powder of ferrous sulfate for injection, and the freeze-dried powder of ferrous sulfate for injection is prepared by freeze-drying a ferrous sulfate solution consisting of ferrous sulfate heptahydrate, sulfuric acid, and water for injection, in which the mass ratio of ferrous sulfate heptahydrate:sulfuric acid:water for injection is 0.1-0.2 g:0.4-0.85 μg:2 g. A method for using a nanocarbon-iron composite formulation in the preparation of a tumor fever therapeutic agent to be used in combination with tissue heating with near-infrared light.
2. The method according to claim 1, characterized in that the mass ratio of the two is 50:7.5-180.
3. The method of claim 1, wherein the nanocarbon iron composite preparation is prepared by uniformly mixing nanocarbon suspension injection and injectable ferrous sulfate, and the pH value of the preparation is 2-7.
4. The method according to claim 3, characterized in that the nanocarbon suspension injection contains nanocarbon, a suspension aid, physiological saline, a pH adjuster, sodium chloride and water for injection.
5. The method for use according to claim 4, characterized in that the nanocarbon suspension injection solution contains 20 to 100 g of nanocarbon, 17 to 30 g of suspension aid, 2 to 4 g of pH adjuster, 8 to 10 g of sodium chloride per 1000 mL, and the remainder is water for injection.
6. The method according to claim 5, characterized in that the nanocarbon is one or more of nanocarbon particles, carbon nanotubes, carbon quantum dots, graphene, fullerene, nanocarbon rods, and nanocarbon fibers.
7. The method according to claim 5, characterized in that the suspending agent is one or more of poloxamer, PVP C30 (polyvinylpyrrolidone C30), and polysorbate 80.
8. 6. The method according to claim 5, wherein the pH adjuster is any one of sodium citrate, sodium acetate, sodium borate, sodium phosphate, and sodium bicarbonate.
9. A method for preparing a nanocarbon suspension injection, comprising: Step 1) of adding a formulation amount of sodium chloride to the above-mentioned 90% v / v water for injection and stirring until completely dissolved to obtain a salt solution; Step 2) of adding a pH adjuster and a suspension aid in the prescribed amounts to the salt solution obtained in step 1) and stirring until completely dissolved to obtain a secondary raw material liquid; Step 3) of adding the pretreated nanocarbon in the amount of the auxiliary raw material liquid obtained in step 2) and stirring uniformly, and then adding the remaining water for injection to obtain a constant volume solution; The method according to any one of claims 5 to 8, further comprising the step of: homogenizing the constant volume solution obtained in step 3) at a rotation speed of 15,000 to 20,000 rpm for 3 to 10 minutes, homogenizing 1 to 5 times at a pressure of 15,000 to 30,000 psi, filling and sealing the container, and then steam sterilizing the container at 115 to 130°C for 10 to 30 minutes.
10. The method of use according to claim 9, characterized in that the pretreatment in step 3) comprises the steps of: after degreasing the nanocarbon with ethyl acetate, washing with an 8-15% v / v HNO3 aqueous solution in which the ratio of nanocarbon mass to HNO3 aqueous solution volume is 1 g:3-5 / ml; washing the nanocarbon with water until it is close to neutral; washing with a 0.08-0.15 mol / L NaOH aqueous solution in which the ratio of nanocarbon mass to NaOH aqueous solution volume is 1 g:3-5 / ml; and then washing the nanocarbon with water until it is close to neutral.
11. The method for preparing the lyophilized powder of ferrous sulfate for injection comprises: S1) In the water for injection containing 90% of the compound, nitrogen gas is passed through the liquid surface at a flow rate of 4.0 to 5.0 m during the preparation process. 3 / h continuously filling with N2; S2) then adding sulfuric acid to adjust the pH to 2.4-2.8; S3) A step of thoroughly stirring and dissolving the ferrous sulfate heptahydrate in the prescribed amount; S4) Add the remaining sulfuric acid to adjust the pH to 2.8 to 3.0, add the remaining purified water to the total volume, and stir uniformly to obtain a ferrous sulfate solution; S5) The method for using the drug solution according to claim 3, further comprising the steps of filtering the drug solution through a micropore filter, filling and freeze-drying the drug solution, and then inserting a plug under vacuum conditions and closing the cap.
12. In the step S5 of the preparation method for lyophilized ferrous sulfate powder for injection, the lyophilization step is S51 Pre-freezing: Rapidly lower the temperature to -10 to -5°C, keep warm for 1 to 3 hours, then rapidly lower the temperature to -50 to -40°C and keep warm for 1 to 3 hours. S52 Drying: S521: After 2-4 hours, the temperature is increased from -50-40°C to -20-10°C, and then the sample is kept at -20-10°C and 80-120mtorr for 2-4 hours. S522: After 1 to 3 hours, the temperature is increased from -20 to -10°C to -10 to 0°C, and the temperature is maintained at 80 to 120 mtorr and -10 to 0°C for 1 to 3 hours. S523: The method for use according to claim 11, further comprising the step of increasing the temperature from 0°C to 20°C after 3 to 6 hours, and then maintaining the temperature at 80 to 120 mtorr and 20°C for 3 to 6 hours.
Citation Information
Patent Citations
Preparation method of water-soluble magnetic targeting graphene oxide derivative and application thereof
CN103183311A
New uses of nanometer charcoal suspension injection
CN104971365A
Preparation method and application of nano-carbon suspension injection
CN112168775A
Nanocarbon-iron composite system and its composition, preparation method and use
JP2020504155A